Choosing an Accounting Method to Explain Public Policy: Social Return on Investment and UK Non-profit Sector Policy. Issue 2 (15th March 2018) - Hall, Matthew; Millo, Yuval
Abstract: We examine why certain accounting methods are chosen by government policy-makers to explain and rationalize their policy actions. We focus on the case of social return on investment (SROI), an accounting methodology that aims to capture and quantify the value created by social purpose organizations, and employs techniques of monetization and the expression of value as a ratio of benefits for investments [see REDF. (2000). SROI methodology: Analyzing the value of social purpose enterprise within a social return on investment framework . San Francisco: REDF; New Economics Foundation (NEF). (2007). Measuring real value: A DIY guide to social return on investment ]. In particular, we examine how and why SROI was chosen for explaining and rationalizing the UK Government's policy of greater involvement of non-profit sector organizations in public service delivery. Our central contribution is to propose two important factors, which we identify as the capturability and communicability of accounting methods, that help to explain why a particular accounting method would be chosen by policy actors to explain and rationalize their public policy choices. The research helps further our understanding of the intersection between accounting and public policy by focusing explicitly on accounting's important role in explaining and rationalizing public policy.